Repression of the stress granule protein G3BP2 inhibits immune checkpoint molecule PD‐L1 - Yanhong Zhang; Changli Yue; Anna M. Krichevsky; Igor Garkavtsev (Molecular Oncology)
Mounting evidence suggests that cancer stemness and immunosuppression are related, but the underlying mechanisms behind these are not clear. We previously reported that the stress granule‐associated protein G3BP2 is involved in the regulation of tumor‐initiating (stem) cells. In this study, we show that this protein also upregulates the immune checkpoint molecule PD‐L1 under conditions of stress in breast and glioblastoma cancer cells, revealing a previously unknown connection between stemness programs, stress responses, and immune checkpoint control. We also identified a significant correlation between G3BP2 and PD‐L1 co‐expression in tumor tissues from cancer patients. To assess the targetability of G3BP2, we employed a small molecule (C108) that binds G3BP2 and interferes with the stress response. Tumors treated with C108 had increased CD8 T‐cell proliferation and infiltration. Moreover, treatment of breast tumor‐bearing mice with C108 resulted in a significant survival benefit and long‐term cures. Cancer cells treated with C108 or cancer cells with genetically repressed G3BP2 had decreased PD‐L1 expression due to enhanced mRNA degradation. Our study provides a compelling mechanism linking stress granule formation and immune checkpoint program of cancer, suggesting this link may provide new opportunities for improving anticancer immunotherapy.